Rediseño del sistema de operaciones para la optimización del mantenimiento de herramientas de perforación en una empresa de servicios petroleros. (2022)
The redesign of operations for the optimization of the maintenance of drilling tools in an oil services company was carried out based on an initial diagnosis of the current situation of the work area, so that through the implementation of the principles of LEAN Manufacturing and the evaluation and proposal of a new plant distribution could obtain solutions that reduce non-productive times in operations, generating an action plan that in the future can be implemented, monitored, evaluated and maintained over time through key performance indicators that allow to measure the efficiency, effectiveness and productivity of the operations.